Comparison of the effect of intermittent hypoxic training vs. the live high, train low strategy on aerobic capacity and sports performance in cyclists in normoxia - Czuba, M.; Fidos-Czuba, O.; Ploszczyca, K.; Zajac, A.; Langfort, J. (Biology of Sport, 2018)
The aim of the study was to compare the effect of intermittent hypoxic training (IHT) and the live high, train low strategy on aerobic capacity and sports performance in off-road cyclists in normoxia. Thirty off-road cyclists were randomized to three groups and subjected to 4-week training routines. The participants from the first experimental group were exposed to normobaric hypoxia conditions (FiO2 = 16.3%) at rest and during sleep (G-LH-TL; n=10; age: 20.5 ± 2.9 years; body height 1.81 ± 0.04 m; body mass: 69.6 ± 3.9 kg). Training in this group was performed under normoxic conditions. In the second experimental group, study participants followed an intermittent hypoxic training (IHT, three sessions per week, FiO2 = 16.3%) routine (G-IHT; n=10; age: 20.7 ± 3.1 years; body height 1.78 ± 0.05 m; body mass: 67.5 ± 5.6 kg). Exercise intensity was adjusted based on the lactate threshold (LT) load determined in hypoxia. The control group lived and trained under normoxic conditions (G-C; n=10; age: 21.8 ± 4.0 years; body height 1.78 ± 0.03 m; body mass: 68.1 ± 4.7 kg; body fat content: 8.4 ± 2.4%). The evaluations included two research series (S1, S2). Between S1 and S2, athletes from all groups followed a similar training programme for 4 weeks. In each research series a graded ergocycle test was performed in order to measure VO2max and determine the LT and a simulated 30 km individual time trial. Significant (p<0.05) improvements in VO2max, VO2LT, WRmax and WRLT were observed in the G-IHT (by 3.5%, 9.1%, 6.7% and 7.7% respectively) and G-LH-TL groups (by 4.8%, 6.7%, 5.9% and 4.8% respectively). Sports performance (TT) was also improved (p<0.01) in both groups by 3.6% in G-LH-TL and 2.5% in G-IHT. Significant changes (p<0.05) in serum EPO levels and haematological variables (increases in RBC, HGB, HCT and reticulocyte percentage) were observed only in G-LH-TL. Normobaric hypoxia has been demonstrated to be an effective ergogenic aid that can enhance the exercise capacity of cyclists in normoxia. Both LH-TL and IHT lead to improvements in aerobic capacity. The adaptations induced by both approaches are likely to be caused by different mechanisms. The evaluations included two research series (S1, S2). Between S1 and S2, athletes from all groups followed a similar training programme for 4 weeks. In each research series a graded ergocycle exercise test was performed in order to measure VO2max and determine the lactate threshold as well as a simulated 30 km individual time trial.